International gaharu trade and its implication on harvesting to the local communities / Mohd Parid M and Lim. H.F. - M., Mohd Parid; Lim,, H.F. (2002)
Gaharu is one of a few of the international non-timber forest products well known for its resinous, fragrant and highly valuable heartwood produced by the Aquilaria spp. of the family Thymelaeaceae. The formation of the resinous within the tree is always associated with some external injury to the timber and is never produced in sound tree where no injury occurs. Eight tree species of Aquilaria are found distributed throughtout India, China, Southeast Asia and the East Indies. There has been active trading and demand for gaharu with the introduction of new applications for gaharu materials in the cosmetical industry, manufacturing and other products. Because of the very high demand of this material, it has contributed to the national and household economy especially among gaharu collectors. Gaharu contributed to the national income through export. The total net trade of gaharu in raw and semi-processed form (i.e. timber, chips and powder) was over 1,350 tonnes from 1995 to 1997. This trade data is only a fraction of the total world trade in gaharu, as demostrated by Customs import data from Taiwan which show imports totalling approximately 2,050 tonnes during the same period. Indonesia and Malaysia were reported to be the main exporters with the total export of approximately 923 tonnes and 341 tonnes, respectively from the year 1995 to 1997. These two countries are the primary suppliers of these material to international market. The major importer countries are Hong Kong, Taiwan, Japan, Singapore, Saudi Arabia, Yemen, Oman and UAE. In the global market there are many form of gaharu traded, ranging from large sections of trunk to finished products such as incense and perfumes. Generally the most common forms in trade are gaharu chips and flakes. Although the overall trade volumes of these materials may appear small in timber trade term but they are not small in monetary terms. Gaharu chips and flakess may sell for several hundred to several thousand US dollars per kilogramme. The price of oil distilled from gaharu is generally between five and ten thousand US dollars per kilogramme, but can be more than that espeacially for gaharu oil of exceptionally high quality. The objective of this paper is to review the potential of gaharu in international trade and its importance to household economy. It provides information in terms of the status of these resources in the market and also provide better understanding of the value of the gaharu to the local communities. In 1999, our case study in Terengganu showed that the involvement of villagers in these activities generated a reasonable average level of income, comprising about 62% from the total household income. These materials were sold at prices varying from around RM8-4, 000 per kilogramme depending on the grade. The classification (grading) of gaharu in the international market is depend on a complex set of factors related to the colour, species involved, size, fragrance and resin content of gaharu offered for sale.